A THERMOMECHANICAL STRESS CRITERION FOR FAILURE OF SURFACE-COATED MATERIALS IN CONCENTRATED SLIDING CONTACTS - AHN, HS (ELSEVIER SCI LTD, 1993)
A recently developed procedure for determining the combined thermal and mechanical stresses in concentrated sliding contacts has been utilized to predict the failure condition of layered solids. By relating the stress condition in the contact to the local strength of the material when specified in terms of its yield strength, it is possible to predict the onset of surface damage caused by the transition from mild to severe wear under dry sliding conditions of operation. The influence of various factors on the failure criterion has been investigated; these include the thermal and mechanical properties of both layer and substrate material as well as the operating conditions and layer thickness. The results are presented in terms of graphs depicting the stress behaviour on the contact surface and in the subsurface as a function of various factors mentioned above.
Keywords: SEAL